(untitled) (Annals of Medical Research, 2022)
Aim: The purpose of the present study is to examine the motor imagery profiles of children with hemiplegic cerebral palsy. Materials and Methods: 52 Hemiplegic (29 males, 23 females) individuals with 11.35 ± 3.48 years of mean age were included in the research. Participants’ implicit motor imagery abilities were analyzed with the laterality task. In addition, weekday and weekend screen times were questioned. Results: No statistically significant difference was determined in motor imagery abilities in terms of gender and affected extremity (p>0.05). Additionally, a significant correlation was found between screen time and Laterality task affected side accuracy and Laterality task not affected side accuracy percentages in both females and males (p<0.05). A significant correlation was found between age and motor imagery skills of males and left hemiplegic individuals. Conclusion: Excessive screen times negatively affect motor imagery abilities in Hemiplegic Cerebral Palsy. It was observed that motor imagery skills were associated with age, but not with gender and affected sides.